Surgery of Intramedullary Tumours - Julius July (Neurologico Spinale Medico Chirurgico, 2018)
Surgery still offers a cure to the majority of intramedullary tumours. The challenge of the surgery is taking out the tumour while preserving the function. Very often the patient has a huge tumour with very minimal symptoms, such as mild numbness. The slow growth of the tumour nature provides enough time for the cord fibres to adapt accordingly. Usually, the motor function is preserved and most of the pathologies are benign. For this reasons, the majority of cases have good long-term tumour control. The functional outcome is depending on the preoperative functional state, especially for motor function. The patient should be educated prior to surgery, especially to anticipate the post-surgical rehabilitation period. The surgical technique should preserve the motor function, but the fine movement usually gets worst for several months after surgery and slowly recover within 6 months. We share our experience of 45 surgical cases with intramedullary tumour (14F;31M), the pathologies distributions are 20 ependymomas, 8 astrocytomas (1/8 anaplastic astrocytoma), 7 cavernomas, 8 hemangioblastomas, 1 glioblastoma multiforme, and 1 tuberculoma. The location distribution varied from 27 at the cervical cord, 11 thoracal, 4 thoracolumbal, and 3 MO-upper cervical. The surgical outcome for all cases experienced sensory changes and recovered over 6 months. Almost all cases experienced some degree of spasticity and fine movement difficulty and they are improving over 6 months. Motor strength is usually preserved. One case of GBM, improve gradually for the first two months then followed by the disease course regardless of the treatment. The tuberculoma case required one year to recover her neurological function with adequate treatment.